Seroepidemiological Study of Canine and Human Dirofilariasis in the Endemic Region of Northern Serbia - Savić, Sara; Stosic, Marina Zekic; Marcic, Doroteja; Hernández, Isabel; Potkonjak, Aleksandar; Otasevic, Suzana; Ruzic, Maja; Morchón, Rodrigo (Frontiers in Veterinary Science, 2020)
Dirofilariosis is a vector borne zoonotic diseases caused mainly by Dirofilaria immitis and Dirofilaria repens that affect dogs and humans all over the world. Serbia is considered as an endemic country to both forms of dirofilariosis although the majority of the population is concentrated in the north of the country. The aims of this study was to show the prevalence of D. immitis and D. repens in dogs and the seroprevalence in humans compared to last studies in the Northern Serbia. We analyzed a 346 dog sera samples and 265 human samples. On the one hand, dogs blood samples were analyzed by modified Knott to check whether there were Dirofilaria spp. microfilariae and serum samples were checked by a commercial D. immitis antigen test. On the other hand, human serum samples were analyzed using a non-commercial ELISA to detect the specific anti-D. immitis, anti-D. repens and anti-Wolbachia IgG antibodies, and confirmed by Western blot. The overall prevalence for Diroflilaria spp. in dogs was 29,19%. The overall prevalence for D. immitis was 26.30%. The percentage of D. immitis and D. repens microfilaremic dogs was 25.72%, and 1.45% recpectively, and for D. immitis/D. repens microfilaremic co-infections was 1.45%. The orevall seroprevalence for Diroflilaria spp. in humans was 3.77%. The overall seroprevalence for D. immitis was 1.51%, for D. repens 1.13%, and D. immitis/D. repens co-infections was 1.13%. The results indicate that D. immitis and D. repens are present in dogs and humans in the province of Vojvodina, in the Northern part of Serbia. It is most probably associated with the presence of many rivers, climate, presence of mosquitoes, so there's a real Public Health risk.